Archeology in the training of museologists: a view from the Museum Studies Course (1932-2010) (Cadernos de Sociomuseologia, 2016)
Since 1932, the Museum Studies Course , originally linked to the National History Museum (MHN / Ibram / Ministry of Culture ) and , since 1979, member of the Federal University of the State of Rio de Janeiro ( UNIRIO ) , is committed to the challenge of training professionals to act in the preservation, research and communication of the museum heritage of the country . The research group "Memory and Museology Preservation in Brazil, coordinated by Prof. Dr. Ivan Coelho de Sá ( CCHS / UNIRIO ) , has been conducting studies in order to understand the configuration of the field of Museology and reflect on the following routes. In this sense, a research was developed in order to realize the place of archeology in the training of museum experts from the analysis of the curricula of Museology course founded in 1932. The purpose of this article is precisely to present some of the results obtained with the development of the study, among which is the realization of the importance of the study of the foundations of archeology in the training of museum experts, which contributed to the creation of professionals who not only worked in both fields of knowledge but, above all, the preservation of archaeological heritage. Keywords: Museology; Archaeology; course of museologists